“Probing in the complexities of the integrated undergraduate medical curriculum”: A qualitative exploratory study - Shaheen, Neelofar; Ahmed Khan, Rehan; Yasmeen, Rahila; Tanveer Sajid, Muhammad (Journal of the Pakistan Medical Association, 2021)
Objectives: To explore the perceptions of the faculty regarding the level of curriculum integration and their interpretation of the integration ladder in achieving the complex process. Method: The qualitative exploratory study was conducted at Islamic International Medical College Islamabad, University College of Medicine and Dentistry Lahore and Rehman Medical College Peshawar, from March to August 2018. The participants were the faculty members involved in the designing and implementation of the integrated curriculum in these institutes. The semi-structured interviews were audio-recorded, transcribed and analysed using Braun and Clarke’s thematic content analysis. Results: Of the 18 faculty members, 6 (33.3%) belonged to each of the three institutions. Four themes identified were: curriculum planning, an uphill task; dream versus ground reality; moving up and down the ladder; and teamwork in the paradigm shift. There were different perceptions of the level of integration among faculty members within the same institute. The level of integration ranged from 5-9 in different phases of the curriculum. The processes included all the teamwork steered by the departments of medical education. Conclusion: Although Harden’s integration ladder is a useful tool, curriculum integration is an inherently inconsistent and complex process that does not follow a simple hierarchical continuum of integration and requires a teamwork. Identifying the patterns of integration in different phases of the curriculum might be more practical than just determining a single level of integration in the whole curriculum. Key Words: Curriculum, Integration, Faculty, Pakistan.